Plan de recuperación de servicios ecosistémicos del Campus CEASA en base a información paisajística y espectral - Pruna Tapia, Bryan Andrés (2018)
The recovery plan for ecosystem services of the CEASA campus, based on landscape and spectral information at the Technical University of Cotopaxi was oriented to the planned recovery of ecosystem services. The landscape information was based on an AUTOCAD map, and GPS survey of the current area. The spectral information was based on satellite images LANDSAT 8, bands 2 (Blue), 4 (Red), 5 (Near Infrared) and 8 (Panchromatic), corresponding to December 2017. Based on this information, maps of current use were generated and potential soil, with reference to escosystemic services. The current use of land prioritizes agricultural production giving emphasis to the ecosystem services of Food Supply with an area of 16498.71 m2 and Raw Material with an area of 113131.94 m2 and 97957.10 m2 in Infrastructure. 566469.96 m2 are allocated to Habitat Support Services for species, and 33341.12 m2 for carbon sequestration and storage Regulation Services. For Cultural Services Recreation activities and physical and mental health has an area of 17343.98 m2, obtaining 6.78 m2 per person compared to 9 m2 per person recommended by WHO (World Organization for Health). It is recommended for cultural services of recreation and health, physical and mental activities to allocate an area of 21631.24 m2, obtaining 9.85 m2 per person allowing within the ranges recommended by the WHO (World Organization for Health). For aesthetic appreciation and inspiration for culture, art, design and research, an area of 8101.39 m2 should be allocated. The area destined for Regulation is maintained: Carbon sequestration and storage. The vegetation cover shows EVI values for both cultivation areas and EVI for arid areas, shows values of 2.5 to 5 for arboreal and shrub zones, values of 0 for infrastructure. It is recommended to generate the institutional planning within these variables for sustainable campus.